Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 7 - Section 7.1 - Integration by Parts - 7.1 Exercises - Page 476: 21



Work Step by Step

Choose $u=xe^{2x}$ and $dv={(1+2x)}^{-2} \ dx$. To solve for $du$, use the product rule. $$\frac{d}{dx}xe^{2x}=2xe^x+e^{2x}=(2x+1)e^{2x}$$ Solving for $v$: $$\int(1+2x)^{-2} \ dx=\frac{-1}{2(1+2x)}$$ Now apply the integration by parts formula ($uv-\int v \ du$) $$\frac{-xe^{2x}}{2(1+2x)}-\int \frac{-1}{2(1+2x)} \cdot (2x+1)e^{2x} \ dx$$ $$=\frac{-xe^{2x}}{2(1+2x)}+ \frac{1}{2} \int e^{2x} \ dx$$ $$=\frac{-xe^{2x}}{2(1+2x)} + \frac{1}{4} e^{2x} +C$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.